Development strategy of builders in economic dynamics - Bielienkova, O.; Tsyfra, T. (Ways to Improve Construction Efficiency, 2019)
The issues related to the formation of the strategy of developers in the housing market are considered. The analysis of competition in the markets of ten regions of Ukraine by concentration indicators in 2018-19 was conducted. The data on construction of facilities in ten regions were selected for analysis, namely: Vinnytsia, Zhytomyr, Transcarpathian, Ivano-Frankivsk, Mykolaiv, Poltava, Ternopil, Kharkiv , Cherkasy Oblast and Kyiv and developers engaged in the construction of these facilities by concentration indices CR-3, CR-5, CR-7. A methodological approach is proposed to formulate the strategy of the developer in markets with different development of competition - from monopoly to perfect competition. An example is the development of a matrix-based strategy that enables the management or development strategies to be selected based on an assessment of the values of a set of factors that can be identified at the time of analysis. Factors, depending on the selected matrix include: strategic and competitive position of the company; attractiveness of industry and market; balance of business set; parameters of the evolutionary status of industries, enterprises, their businesses and products; the status of key competences and their relevance to the organization’s business and mission. Given the above factors, the appropriate quantitative targets of the enterprise are determined, short and medium term plans are being drawn up. But a static approach may not always take into account the ability to achieve the goals set for the enterprise, because it does not take into account the pace of development (growth or decline in activity) or the dynamics of the enterprise. In order to take into account the economic dynamics, it is proposed to consider the strategy matrix in three-dimensional space, where the third value should be - the rate of development of the enterprise in comparison with the rate of development of the industry. Appropriate coefficients and rating scale are proposed. Strategic (indicated by arrow) and tactical decisions are identified for each quadrant in the matrix to help improve the market position of the object. The use of a matrix of choice of market position in the light of economic dynamics allows to predict the "critical path" for the future and to identify the threshold of opportunities of the developer in the housing market.